Akcja dekrucyfikacyjna w 1958 roku na terenie powiatu sandomierskiego - Tylec, Piotr (Pamięć i Sprawiedliwość, 2017)
The paper presents the course of decrucification action in Sandomierz County located in former Kielce voivodeship. The action was planned by communist authorities and legally based on the Circular no. 26 of the Ministry of Education dated 4 August 1958. In order to present the course of the action, the author needed a query of source materials: KP PZPR and Department of Education of PPRN in Sandomierz, security force act and local Bishop Curia. The author shows all stages of decrucification action carried out on a country level. The first one were preparations, consisting of meeting KP PZR executive, trainings for school directors and state institutions. Another stage was to remove crosses from common schools and state institutions, which did not take place without argument. At the end of the decrucification action, summaries and evaluation concluded that removal of crosses had gone without major problems. In order to present a full picture of the described action, the author presented an outline of the introduction process of Circular 26 by Ministry of Education on 4 August 1958 and discussed the school network of Sandomierz County. The paper is another attempt to show the ways communist authorities fought the Catholic church after the II World War.